Thermo-economic evaluation of banana waste pyrolysis plant for biofuel production (2021)
Health and environmental problems are presented in the world due to gases produced during the combustion of fossil fuels. This problem has focused on researching the production of renewable fuels from biomass. One type of biomass are wastes produced during culture of banana which its industry for every tonne of banana harvested there are, on average, four tonnes of wastes which also contaminated environment. This paper aims to evaluate the economic and exergetic viability of a banana waste pyrolysis plant in Colombia. The processes of the plant were simulated on Aspen Plus®, which solved material and energy balance. The yield of products was validated with experimental results from literature, where differences could be attributed to biomass composition and reactor type. The results obtained revealed yields of 40.20%, 24.75% and 35.07% from bio-oil, char and gas respectively. Economic and exergy data were combined for an exergy costing method to carry out the exergoeconomic analysis. The overall exergy efficiency of the plant was 61.76%. The highest exergy destruction is located in the dryer and the pyrolysis reactor, which accounts for 35.84% and 32.96% respectively. The combustion chamber has the highest exergy destruction cost (180.19 $/h) and a low value of the exergoeconomic factor (5.96 %), indicating that an improvement of the equipment is required, even though this means an increment in cost investment. The study reveals, that the analysis made demonstrates the potential of bio-oil production from banana wastes, and also the possibility to use gases products in a combined heat and power plant. In addition, the study evidence in which process it is necessary to achieve better results of efficiencies in order to improve the whole plant.